The Role of Green CSR, Corporate Image, and Sustainability Motivation on Sustainability Behavior and Environmental Performance Among Hotels in National Capital Region, Philippines - Masa, Jan Racky; Muya, Gerby R. (International Journal of Sustainable Competitiveness on Tourism, 2025)
Recognizing the substantial environmental footprint of hotel operation ranging from resource consumption to waste generation, This study explores the role of green corporate social responsibility on the environmental performance of hotels, highlighting the role of corporate image and sustainability motivation towards the formation of sustainability behavior among employees. The study employs a causal predictive quantitative design. A multistage sampling technique was utilized to collect 446 valid responses from hotel employees and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that green CSR strongly enhances corporate image (β = 0.727; f² = 0.528, large), with smaller but significant direct effects on sustainability motivation (β = 0.205; f² = 0.121, small), influencing positive employee engagement in sustainability-driven behaviors (β = 0.182; f² = 0.091, small), leading to enhanced environmental performance of hotels (β = 0.193; f² = 0.094, small). The results of the mediation analysis indicated that corporate image and sustainability motivation play a complementary and synergistic role in the relationship between green corporate social responsibility and sustainability behavior among hotel employees, leading to enhanced environmental performance (β=0.067; f²=0.033; p=.002). Furthermore, the result indicate that strong green CSR enhances corporate image leading to a multiple serial mediating effect that strengthen employee’s sustainability motivation and sustainability behavior, ultimately predicting improve environmental performance. This research bridges theoretical gaps by providing empirical evidence that supports the mechanism of multidimensional factors influencing employee sustainability behavior and environmental performance. These findings provide valuable insights to hotel management on the development of an employee service-oriented sustainability framework in advocating for green human resources and organizational strategies to foster sustainable hospitality practices.